Single-isocenter versus multiple-isocenters for multiple lung metastases: Evaluation of lung dose. (January 2022) - van Timmeren, Janita E.; Ehrbar, Stefanie; Chamberlain, Madalyne; Mayinger, Michael; Hoogeman, Mischa S.; Andratschke, Nicolaus; Guckenberger, Matthias; Tanadini-Lang, Stephanie
Highlights: Dosimetric comparison of single-isocenter and multiple-isocenters in lung SBRT. Largest differences between the two planning techniques observed in low-dose region. Mean lung dose increased on average by 0.4 Gy compared to multiple isocenters. Estimated risk of radiation pneumonitis increased on average by 1.0% Abstract: Background and purpose: A potential challenge in single-isocenter multi-lesion lung stereotactic body radiotherapy (SBRT) is that patient positioning is not based on each lesion individually, but on the average position of all lesions. This may lead to larger margins compared to treating with one isocenter per lesion, but increases workflow efficiency. The aim of this study was to investigate whether a single-isocenter technique leads to increased normal lung dose compared to a conventional multiple-isocenters technique. Materials and methods: A cohort of 15 NSCLC patients with two or three lesions previously treated with SBRT was subjected to treatment planning with a multiple-isocenter technique and a single-isocenter technique. For the latter, two margin approaches were evaluated: (1) identical margins for each internal target volume (ITV), assuming an average registration for all lesions in cone-beam CT (CBCT) positioning verification and (2) a smaller margin for the largest lesion, assuming an optimal registration for that lesion. For all 45 treatment plans, mean lung dose (MLD) and lungs-V20Gy were evaluated. The study was performed following RATING guidelines. Results: The MLD was 4.9 ± 1.9 Gy (mean ± SD) for multiple-isocenters and 5.4 ± 2.1 Gy and 5.3 ± 2.2 Gy for single-isocenter approach 1 and 2, respectively. V20Gy was 5.5 ± 3.7%, 5.5 ± 3.2% and 5.4 ± 3.3%. A median [range] increase in MLD of 11.6% [−14.9 – 26.8] was observed when comparing single-isocenter treatment plans to those with multiple isocenters. V20Gy increased by 0.2 [−3.4 – 1.3] percentage points. Conclusion: A single-isocenter SBRT technique for lung patients with multiple targets results in clinically acceptable increases in normal lung dose.